Impact of school location and professional qualification on level of giving feedback among primary school mathematics teachers in oral questioning process - Md. Yunus, Aida Suraya; Mahmud, Muhammad Sofwan; Sulaiman, Tajularipin; Mohd Ayub, Ahmad Fauzi (Centro de Investigaciones en Ciencias Sociales y Humanidades America Latina, 2019)
The purpose of this study is to explore the impact of school location and professional qualification on levels of giving feedback among primary school mathematics teachers in oral questioning. This study is a quantitative study using survey methods. Questionnaires were used in this study to collect data on the level of giving feedback in the verbal questioning of primary school teachers and to see the difference in the level of responding to verbal questioning based on school location and professional qualification of mathematics teachers (with Cronbach’s alpha value of 0.91). A total of 154 primary school mathematics teachers around the state Negeri Sembilan were selected as samples for this study using simple random sampling methods. The findings were analyzed using descriptive statistical analysis and inferential statistical analysis to answer the research questions. Based on two-way ANOVA test, the interaction effect between school location and profesional qualification was not statistically significant, F (2, 152) = 1.069, p = 0.346. Besides, there was no statistically significant main effect for school location F (1, 152) = 0.741, p = 0.391 and professional qualification F (2,152) = 2.244, p = 0.110 on levels of giving feedback in oral questioning activity among primary school mathematics teachers. The importance of this study is it provides guide and understanding of primary school mathematics teachers to improve the practice of feedback in oral questioning during the teaching and learning process of mathematics. Furthermore, there are reasonable implications to be taken into account by the policy makers and implementers associated with teachers’ professional development.